Model-based simulation of hydraulic hoses in an intelligent environment - Grossschmidt, Gunnar; Harf, Mait (International journal of fluid power, 2018)
In this paper, comprehensive mathematical models of hydraulic hoses for fluid power systems and a modelling and simulation technology based on using multi-pole models and intelligent simulation environment are proposed. Principles of composing multi-pole mathematical models for hydraulic hoses with lumped parameters having various causalities are discussed. Computing transient and frequency responses of hydraulic hoses in a visual simulation tool CoCoViLa are considered. The CoCoViLa environment is a visual programming tool, which supports declarative programming in a high-level language and automatic program synthesis. The proposed technology enables to find optimal solutions for hydraulic hoses in design and development of various fluid power systems.